Guide to Project Management Programme Evaluation and Review Technique - Planning Commission (Planning Commission, 1963)
PERT: Programme Evaluation and Review Technique - is a planning technique and tool of management control which uses a net work theory. It is primarily a technique most valuable in planning and programming. Nevertheless, it is a fine tool of management control and also a good prognostic medium. PERT forces logical thought. It compels programme planners to recognize the relationship of the parts to the whole. Hence it is effective as a planning tool.
Planning Commission
Planning Commission